Comparative Epistemological Models of Knowledge Integration in Four State Islamic Higher Education Institutions in Indonesia - Nurul Budi Murtini; Muhammad Arfan Mu’ammar; Abdul Mujib; Irfan Yuhadi; Nira Arumsari (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2025)
Several Indonesian Islamic Higher Education Institutions (Perguruan Tinggi Keagamaan Islam/PTKIN) experienced a transformation from Institut Agama Islam Negeri (IAIN) to Universitas Islam Negeri (UIN) in the early 2000s. This transformation not only involved an institutional change but also marked a significant epistemological shift from a single religious identity toward a multidisciplinary university model that integrates religious and general sciences. This study aims to analyse four models of knowledge integration developed at UIN Sunan Kalijaga, UIN Syarif Hidayatullah Jakarta, UIN Maulana Malik Ibrahim Malang, and UIN Sunan Gunung Djati Bandung. Employing a qualitative comparative approach based on a literature review, this study examines the philosophical foundations, epistemological orientations, and patterns of implementation of each model. The findings indicate that the four models emerged from a shared historical context, namely the transformation from IAIN to UIN, and are grounded in relatively similar philosophical foundations that position monotheism and revelation as central epistemic references. However, these foundations are articulated through different conceptual metaphors and epistemological emphases. The implementation of the models has been institutionalised through curricula, academic policies, and organisational culture. The implications of these models for the transformation of Islamic higher education in the digital and global era are complementary and mutually reinforcing. This study also identifies implementation challenges related to academic governance, curriculum synchronisation, and faculty capacity. Overall, the four models of knowledge integration enrich Islamic higher education by integrating spirituality, scientific rationality, and social responsibility, while highlighting the need to strengthen academic governance and sustainable professional development